2014
DOI: 10.5624/isd.2014.44.1.53
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and configuration of the bifid mandibular canal in Koreans by using cone-beam computed tomography

Abstract: PurposeThis study was performed to investigate the incidence and configuration of the bifid mandibular canal in a Korean population by using cone-beam computed tomography (CBCT) imaging.Materials and MethodsCBCT images of 1933 patients (884 male and 1049 female) were evaluated using PSR-9000N and Alphard-Vega 3030 Dental CT units (Asahi Roentgen Ind. Co., Ltd, Kyoto, Japan). Image analysis was performed by using OnDemand3D software (CyberMed Inc., Seoul, Korea). The bifid mandibular canal was identified and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
104
7
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(139 citation statements)
references
References 17 publications
(50 reference statements)
10
104
7
6
Order By: Relevance
“…The only studies available describe the presence of BMCs on PANs without analysing potential influencing factors. Previous research conducted using various populations have described BMCs on multislice CT and CBCT, 3,[7][8][9][10][11][12][13] and have reported a wide variation in frequency, ranging from 10% 13 to 65%. 3 The present study is in line with Fu et al 10 who identified BMCs in 30.6% of patients and 18.5% of total hemimandibles, and Orhan et al 12 who observed BMCs in 27% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only studies available describe the presence of BMCs on PANs without analysing potential influencing factors. Previous research conducted using various populations have described BMCs on multislice CT and CBCT, 3,[7][8][9][10][11][12][13] and have reported a wide variation in frequency, ranging from 10% 13 to 65%. 3 The present study is in line with Fu et al 10 who identified BMCs in 30.6% of patients and 18.5% of total hemimandibles, and Orhan et al 12 who observed BMCs in 27% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] The reported rate of bifid mandibular canals (BMCs) on PAN ranged from 0.08% to 8.30%, whereas on CBCT, it ranged from 10% to 66%. 3,[7][8][9][10][11][12][13] One type of BMC is the retromolar canal, which ends in the retromolar foramen (RF). CBCT studies 14,15 have reported rates of RF between 16% and 65%, 3,11,[13][14][15][16] similar to dry mandible studies ranging from 1.7% to 72.0%, [17][18][19] whereas PANs have yielded a lower range.…”
Section: Introductionmentioning
confidence: 99%
“…28 The rest 3,18,21,[29][30][31][32][33][34][35][36][37][38][39] of the studies were published in dental journals. Sample sizes ranged from 308 38 to 1933 32 CT images and from 350 39 to 6000 panoramic radiographic images.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…28 The rest 3,18,21,[29][30][31][32][33][34][35][36][37][38][39] of the studies were published in dental journals. Sample sizes ranged from 308 38 to 1933 32 CT images and from 350 39 to 6000 panoramic radiographic images. 21 The studies were conducted in nine different countries: Brazil, 30,34,36,37 Canada, 28 Chile, 39 India, 33 Korea, 29,31,32,35 South Africa, 3 Spain, 18 Taiwan 38 and USA.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation